(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the strategies for increasing state revenues and effective use of funds by the state of the Republic of Uzbekistan. Measures are carried out to optimize peace policies, diversify the economy, introduce technology innovations and implement a financial management system. The study also justifies the need to ensure the targeted and transparent distribution of budget funds, the introduction of digital management technologies, the renewal of modern foundations. Based on the data analyzed, choices and recommendations have been developed in which information about economy peace and social competition can be obtained.